Identification of Misconceptions In Second Class (XI) MA PPKP Darul Ma’la Winong Pati Senior High School Students In Circulation System Materials Using Three Tier Diagnostic Instruments - Wahyuni, Silviani Indah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Misconception is a problem where an individual experiences a misinterpretation related to an understanding that has been agreed upon and is considered correct by experts. The circulation system is one of the biology learning materials with complex concepts and has the potential to create gaps for misconceptions. This study aims to identify misconceptions about the circulation system material in class XI MA PPKP Darul Ma'La Winong Pati students. This type of research is quantitative and uses descriptive and non-experimental methods. The subjects of this study were 30 students from class XI MIA 1 and 2 for the academic year 2021/2022 who were selected by random sampling technique. The instrument in this research is a student's ability test using a three-tier diagnostic test. Based on the results of the study, it was found that misconceptions exist in all concepts of the circulation system material with an average percentage of misconceptions reaching 73.2% (high category). The concept with the highest level of misconception is the blood clotting mechanism by 80% and the lowest is the concept of circulatory function by 53.4%. The cause of this misconception is due to internal factors such as student understanding, as well as external factors, namely the way teachers teach and the use of the internet as a source of information